Production of biologically active human lymphotactin (XCL1) by Lactococcus lactis - Zavala Flores, Laura Mireya; Villatoro Hernández, Julio; Gámez Escobedo, Idalia Analí; Franco Molina, Moisés Armides; Rangel Colmenero, Blanca Rocío; Villanueva Olivo, Arnulfo; Gutiérrez Puente, Yolanda; Montes de Oca Luna, Roberto; Valdés Flores, Jesús; Saucedo Cárdenas, Odila (2009)
Lymphotactin-XCL1 is a chemokine produced mainly by activated CD8? T-cells and directs migration of CD4? and CD8? lymphocytes and natural killer (NK) cells. We expressed human lymphotactin (LTN) by the lactic-acid bacterium Lactococcus lactis. Biological activity of LTN was confirmed by chemo-attraction of human T-cells by chemotaxis demonstrating, for the first time, how this chemokine secreted by a food-grade prokaryote retains biological activity and chemoattracts T lymphocytes. This strain thus represents a feasible well-tolerated vector to deliver active LTN at a mucosal level.